2017
DOI: 10.1080/20742835.2017.1352644
|View full text |Cite
|
Sign up to set email alerts
|

Impact of percutaneous nephrostomy in South African women with advanced cervical cancer and obstructive uropathy

Abstract: Objectives: South Africa women with cervical carcinoma present at younger ages and the majority with advanced-stage disease. Certain patients may have a favourable outcome after placement of a percutaneous nephrostomy (PCN) for obstructive uropathy in cervical cancer. Methods: A retrospective audit was conducted at the Gynaecological Oncology Unit, University of Pretoria. All patients with primary untreated cervical cancer with renal impairment secondary to obstructive uropathy were included. Urea, creatinine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Consequently, it can be argued that business incubation expands entrepreneurial capabilities beyond mere entrepreneurship learning because it provides access to other relevant resources. This capability set includes certain entrepreneurial and managerial competencies (Morris et al, 2013), as well as access to relevant physical, informational, financial and other resources needed for entrepreneurial success (Van Aardt et al, 2008).…”
Section: Expanding Capabilities Through Business Incubationmentioning
confidence: 99%
“…Consequently, it can be argued that business incubation expands entrepreneurial capabilities beyond mere entrepreneurship learning because it provides access to other relevant resources. This capability set includes certain entrepreneurial and managerial competencies (Morris et al, 2013), as well as access to relevant physical, informational, financial and other resources needed for entrepreneurial success (Van Aardt et al, 2008).…”
Section: Expanding Capabilities Through Business Incubationmentioning
confidence: 99%
“…On the other hand, complications of percutaneous nephrostomy seem to be high as the rates of urinary tract infections range between 20 and 50% and of postoperative ureteral obstruction due to advancing disease of catheter dislodgement between 10 and 40%. 8,25,37-39 Nevertheless, in their majority they seem to be of mild to moderate severity and; thus, do not affect the quality of life of patients. However, since 1996, Emmert et al .…”
Section: Discussionmentioning
confidence: 99%
“…41 Recently van Aardt confirmed this hypothesis as they also observed that nephrostomy may benefit patients with uremia and primary untreated locally advanced disease, as it may restore blood urea nitrogen levels to normal and; thus, permit the implementation of chemotherapy and radiotherapy that may prolong the survival of these patients. 8 Taking this latter information into account it seems obvious that more information is needed to clarify if obstructive uropathy has the same impact among patients with stage IIb, III and IVa cervical cancer. To date, it is well known that these subgroups of patients have different 5-year survival outcomes and it would be of significant benefit if research would effectively designate whether this is primarily the result of obstructive uropathy, which is generally expected to be more prevalent in patients with stage ≥III disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although urinary diversion procedures can certainly improve the quality of life of advanced cervical cancer patients, current evidence suggests that urinary diversion does not significantly increase the survival rate of cervical cancer patients (Pergialiotis et al, 2019). In addition, several complications, although rare, have been associated with the nephrostomy procedure in cervical cancer, including pneumothorax, bowel injury, pararenal abscess, pyelonephritis, and urinoma (Van Aardt et al, 2017). This study, therefore, aims to identify the determinants of survival rate in cervical cancer patients undergoing nephrostomy for obstructive uropathy, and identify the subset of patients that would benefit the most from this procedure.…”
Section: Factors Affecting Survival Outcome After Percutaneous Nephrostomy As Palliative Urinary Diversion In Obstructive Uropathy Due Tomentioning
confidence: 99%